2015
DOI: 10.1002/2014wr015716
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of atmospheric nitrate processing and export in forested catchments

Abstract: Increased deposition of reactive atmospheric N has resulted in the nitrogen saturation of many forested catchments worldwide. Isotope-based studies from multiple forest sites report low proportions (mean 5 10%) of unprocessed atmospheric nitrate in streams during baseflow, regardless of N deposition or nitrate export rates. Given similar proportions of atmospheric nitrate in baseflow across a variety of sites and forest types, it is important to address the postdepositional drivers and processes that affect at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 127 publications
(265 reference statements)
5
105
1
2
Order By: Relevance
“…By determining both concentration and the 17 O-excess of stream nitrate, we can quantify unprocessed NO 3 − atm in stream water accurately and precisely. Recent studies on nitrate including unprocessed NO 3 − atm exported from forested catchments via streams during base flow period have revealed that the export flux of unprocessed NO 3 − atm increases in accordance with increases in the stream nitrate concentration (Rose et al, 15 2015a; Rose et al, 2015b;Tsunogai et al, 2014). These results implied that unprocessed NO 3 − atm exported from forested catchments can be used as a tracer to identify the biological processing of nitrate in each catchment area and to clarify the processes regulating nitrate concentrations in stream water.…”
Section: Stream Nitrate Being Exported From Forested Watersheds 10mentioning
confidence: 99%
“…By determining both concentration and the 17 O-excess of stream nitrate, we can quantify unprocessed NO 3 − atm in stream water accurately and precisely. Recent studies on nitrate including unprocessed NO 3 − atm exported from forested catchments via streams during base flow period have revealed that the export flux of unprocessed NO 3 − atm increases in accordance with increases in the stream nitrate concentration (Rose et al, 15 2015a; Rose et al, 2015b;Tsunogai et al, 2014). These results implied that unprocessed NO 3 − atm exported from forested catchments can be used as a tracer to identify the biological processing of nitrate in each catchment area and to clarify the processes regulating nitrate concentrations in stream water.…”
Section: Stream Nitrate Being Exported From Forested Watersheds 10mentioning
confidence: 99%
“…Several types of active radars overcome the drawbacks of optical sensors, although all current systems also have limitations of their own [Smith, 1997;Calmant et al, 2008;Schumann et al, 2009]. Radar altimetry measurements from sensors such as Jason-2 and Envisat provide point-based measurements of river WSEs, which can be used to interpolate slopes and develop stage-discharge relationships [O'Loughlin et al, 2013;Paris et al, 2016]. However, altimeter observations have low spatial and temporal resolutions, with vertical errors of decimeters to meters [Calmant et al, 2008;Biancamaria et al, 2016a;O'Loughlin et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies using Δ 17 data reported that NO 3 -N Atm made up 5-10% of total NO 3 -N in streams, groundwater, and/or soils within temperate forest ecosystems [Costa et al, 2011;Tsunogai et al, 2010], whereas Rose et al [2015aRose et al [ , 2015b reported up to~50% NO 3 -N Atm in a stream draining a conifer-dominated watershed. These studies, along with qualitative evidence for NO 3 -N Atm in base flow based on δ 18 O-NO 3 À data [Rose et al, 2015b;Sebestyen et al, 2014], have suggested that the loss of unprocessed, deposited N can occur outside of direct runoff producing events [Curtis et al, 2011]. However, prior studies were not specifically designed to quantify intra-annual and inter-annual variation in the export of NO 3 -N Atm and NO 3 -N Micro in streams during a range of hydrological conditions.…”
Section: Introductionmentioning
confidence: 99%